Hubungan Personal Hygiene Dengan Kejadian Kecacingan Pada Anak Usia 6-9 Tahun Di Desa Pesarean Pagerbarang Tegal Jawa Tengah - Khasanah, Isma Laelatul; Khusna , Umi Nihayatul; Jaman , Anwar (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2025)
Background: Ringworm disease is one of the diseases caused by infections with Soil Transmitted Helminths (STH) which usually attacks children because they are less able to maintain Personal Hygiene such as still liking to play in the soil,and not washing hands after playing.Objectives: : The aim of this research is to determine the relationship between personal hygiene and the incidence of worms in children aged 6-9 years in Pesarean Pagerbarang Village, Tegal, Central Java.Materials and Methods: This study uses an Observational Analytical research type using a cross-sectional approach , with a Incidental Sampling technique.Results: Based on the results of the questionnaire interview, it was found that 17 children (48.57%) had good personal hygiene, and 18 children (51.43%) had poor personal hygiene. Laboratory examination showed that 21 children (60.00%) were infected with STH, including Ascaris Lumbricoides, 18 children (85.71%). Tricuris Trichiura 1 child (4.76%), Necator Americaanus 2 children (9.52%). Conclusions: The results of analysis using chi-square obtained p-value = 0.000 for the relationship between personal hygiene and the incidence of worms and p-value = 0.013 for the relationship between nail cleanliness and the incidence of worms. This shows that there is a significant relationship between the two because ?<0.05. Keywords Incidence of worms; Personal hygiene..